The relationship of physical literacy, physical activity, physical fitness to the psychological well-being of students - Mohammad Irfan (Universitas Muhammadiyah Enrekang, 2023)
Psychological towards students is an important component in the process of character education for children, especially in terms of Physical Literacy, Physical Activity, and Physical Fitness. The purpose of this study was to determine the relationship between physical literacy, physical activity, and physical fitness on psychological well-being in students aged 16-18 years. The population and sample involved in the study were 129 subjects. The significance values of 0.000 and 0.000 and 0.860 respectively can be said that there is a significant relationship with physical literacy, physical activity, physical fitness to psychological well-being in students. A person chooses a sport based on knowledge and understanding of the sport he chooses. The level of need of students in receiving physical literacy, physical activity, and physical fitness is an important part in maximizing student motor. In addition to improving motor movements of students, physical literacy, physical activity and physical fitness can provide students with a better lifestyle.